Too Soon to IPO? Commentary in Champion, David (2001) - JONES, Neil (Institutional Knowledge at Singapore Management University, 2001)
Four years ago, Diane Ashton and Sundeep Lai were working together at MIT on a titanium extraction project. Durable and highly heat resistant, titanium is a key constituent of many specialty alloys, but it's also very expensive to produce. So when Diane discovered a solution that isolated titanium efficiently, the partners recognized that the technology would be worth billions to large manufacturers. Sundeep and Diane secured a $20 million investment from a prominent VC and drew up a business plan. Within six months of their discovery, Titrolyte Incorporated was born. But Diane and Sundeep soon discovered that what had been a fairly straightforward operation in the confines of an MIT lab was difficult to reproduce on a large scale. The solution was extremely sensitive to temperature and impurities, and sometimes it simply didn't work. In just two years, they had to go back to investors for more money. They also started a materials-testing business to help generate more cash, and its revenues are expected to touch $10 million this year. On the back of this success, Sundeep thinks that Titrolyte is ready to go public. Besides, he's concerned that if they don't IPO now, they might miss the bus. But Diane is worried that they're moving too fast. They haven't perfected the technology yet, and Titrolyte's business systems leave a great deal to be desired. Their treasury operations are weak, and there's no formal budgeting process, organized health plan, or pension scheme. Should Titrolyte risk going public now, while the market is still open? Five commentators offer advice in this fictional case study.